Using innovative foresight to develop the competitiveness of business structures - Mukhamedkhanova, A.B.; Tulemetova, A.S.; Kulbay, B.S.; Nursoy, M.; Baibosynov, S.B. (BUKETOV BUSINESS REVIEW, 2023)
Object: to show the impact of innovative foresight on business structures and to describe the advantages of innovative foresight. Methods: during the research, various methods were used in the work: analysis, comparison, comparative evaluation of data, review, description, description of data. During the data analysis, plans for the future of the Republic of Kazakhstan for different years were obtained, as well as scientific publications of leading economists dealing with the problems of development and improvement of the market of innovative foresight. Findings: The article discusses common problems. The basic concepts are defined, the importance of using innovative foresight for the development of competitiveness of business structures is determined. Conclusions: on the basis of individual data, an analysis of modern business structures was carried out, as well as an analysis of the prospects and trends of using foresight, it was proved that innovative foresight aimed at increasing the strategic competitiveness of business structures is the most popular tool for research and active construction of prospects for modern enterprises and organizations.